Postoperative Infection in Developing World Congenital Heart Surgery Programs: Data From the International Quality Improvement Collaborative. Issue 4 (April 2017) - Sen, Amitabh Chanchal; Morrow, Debra Forbes; Balachandran, Rakhi; Du, Xinwei; Gauvreau, Kimberlee; Jagannath, Byalal R.; Kumar, Raman Krishna; Kupiec, Jennifer Koch; Melgar, Monica L.; Chau, Nguyen Tran; Potter-Bynoe, Gail; Tamariz-Cruz, Orlando; et al.
Abstract : Background—: Postoperative infections contribute substantially to morbidity and mortality after congenital heart disease surgery and are often preventable. We sought to identify risk factors for postoperative infection and the impact on outcomes after congenital heart surgery, using data from the International Quality Improvement Collaborative for Congenital Heart Surgery in Developing World Countries. Methods and Results—: Pediatric cardiac surgical cases performed between 2010 and 2012 at 27 participating sites in 16 developing countries were included. Key variables were audited during site visits. Demographics, preoperative, procedural, surgical complexity, and outcome data were analyzed. Univariate and multivariable logistic regression were used to identify risk factors for infection, including bacterial sepsis and surgical site infection, and other clinical outcomes. Standardized infection ratios were computed to track progress over time. Of 14 545 cases, 793 (5.5%) had bacterial sepsis and 306 (2.1%) had surgical site infection. In-hospital mortality was significantly higher among cases with infection than among those without infection (16.7% versus 5.3%; P <0.001), as were postoperative ventilation duration (80 versus 14 hours; P <0.001) and intensive care unit stay (216 versus 68 hours; P <0.001). Younger age at surgery, higher surgical complexity, lower oxygen saturation, and major medical illness were independent risk factors for infection. The overall standardized infection ratio was 0.65 (95% confidence interval, 0.58–0.73) in 2011 and 0.59 (95% confidence interval, 0.54–0.64) in 2012, compared with that in 2010. Conclusions—: Postoperative infections contribute to mortality and morbidity after congenital heart surgery. Younger, more complex patients are at particular risk. Quality improvement targeted at infection risk may reduce morbidity and mortality in the developing world.